Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1089/ten.tea.2010.0008
|View full text |Cite
|
Sign up to set email alerts
|

Application of Resorbable Poly(Lactide-co-Glycolide) with Entangled Hyaluronic Acid as an Autograft Extender for Posterolateral Intertransverse Lumbar Fusion in Rabbits

Abstract: Facilitating fusion between bony segments in a reliable and reproducible manner using a synthetic bone graft material has a number of benefits for the surgeon as well as the patient. Although autograft remains the gold standard, associated comorbidities continue to drive the development of new biomaterials for use in spinal fusion. The ability of autograft alone and autograft combined with a radiolucent biomaterial composed of resorbable osteoconductive poly(lactide-co-glycolide) with entangled hyaluronic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 40 publications
6
16
0
Order By: Relevance
“…The accumulation of data on the anti-inflammatory and immunomodulatory roles of MSCs when they are implanted (or injected) in various situations indicates that MSCs would not promote the call of phagocytic cells at the implant site, conversely preventing it [ 41 , 42 ]. Although implanted cells in the same surgical procedure must be right, our observations suggest that perhaps there is a demolition phase before bone formation, with the participation of macrophages and osteoclasts, as has been proposed [ 43 ]. In a study carried out not long ago, researchers significantly improved the ossification of a tibial defect by injecting endothelial progenitors two weeks after wound healing began [ 44 ].…”
Section: Discussionsupporting
confidence: 56%
“…The accumulation of data on the anti-inflammatory and immunomodulatory roles of MSCs when they are implanted (or injected) in various situations indicates that MSCs would not promote the call of phagocytic cells at the implant site, conversely preventing it [ 41 , 42 ]. Although implanted cells in the same surgical procedure must be right, our observations suggest that perhaps there is a demolition phase before bone formation, with the participation of macrophages and osteoclasts, as has been proposed [ 43 ]. In a study carried out not long ago, researchers significantly improved the ossification of a tibial defect by injecting endothelial progenitors two weeks after wound healing began [ 44 ].…”
Section: Discussionsupporting
confidence: 56%
“…Histological observation of sham defects in rabbits revealed an abnormal fatty appearance to the marrow space occupying these defects, with a futile attempt at revascularization. Further confirmation of this mechanism of action was recently obtained in the Boden model for posterolateral lumbar fusion using a mixture of InQu granules and ICBG (50:50 ratio) ( 31 ). Vascularization of a cartilage intermediate was accompanied histologically by calcification of the cartilage matrix, which ultimately was replaced by woven bone from invading osteoprogenitor cells originating from the vasculature ( 31 ).…”
Section: Discussionsupporting
confidence: 54%
“…Color images available online at www.liebertpub.com/tea ‰ ENGINEERED ENDOCHONDRAL CARTILAGE GRAFTS matrix with bone autograft promotes endochondral ossification in a rabbit model of spinal fusion. 31 In conclusion, we have shown that hOA articular chondrocytes from total joint arthroplasty resections can be transformed into endochondral tissues that promote bone formation in vivo. These grafts are able to integrate with host bone, undergo vascularization, and heal critical-size longbone defects in mice.…”
Section: Discussionmentioning
confidence: 73%